Kinetic freeze-out properties from transverse momentum spectra of kaon, pion, and (anti-)proton production in U+U collisions at sNN = 193 GeV - Yuan, Ying (Frontiers in Physics, 2025)
In the framework of the multi-source thermal model employing the Tsallis distribution, the transverse momentum distributions of kaon, pion, and (anti-)proton production in U + U collisions at sNN = 193 GeV with varying centrality are investigated. The transverse momentum spectra are appropriately characterized. The dependencies of parameters (average transverse momenta, effective temperature, and entropy index) on event centrality are determined. It is observed that the q parameters increase as the average number of particles participating in the collisions rises, which implies that the nuclear stopping degree elevates with the increase of collision centrality. The T value remains fundamentally consistent for the same particle under different collision parameters, suggesting that the kinetic freezing temperature of particle ejection in this collision system is independent of the collision parameters. However, the q value exceeded the previously determined research range, which might be related to the deformation of the U-nucleus.